The use of small talk in Arabic and Malay drama: a comparative analysis / Anis Nabilah Mamat - Mamat, Anis Nabilah (2023)
Small talk is a casual conversation between two speakers that aims to increase friendliness and strengthen social relations without conveying any information. It is also one of the language politeness strategies used to initiate communication. In general, this study aims to analyse the comparison of small talk used in the communication between Arabs and Malays. Both cultures have various expressions of small talk which must be understood systematically to avoid cultural conflict, confusions, miscommunication, and misinterpretation. Besides, it is challenging to understand the differences and similarities of small talk expressions between Arab and Malay culture due to a lack of research on the comparative study of Arab and Malay small talk. This study compared the usage of small talk in Malay and Arabic drama from three perspectives namely forms, functions, and gender. In this study, descriptive qualitative approach and content analysis method were both applied. The data of the study came from the Malay drama series "Nur 2" (5 episodes) and the Arabic drama series "أوراق الزمن المر " (5 episodes). Jumanto's (2014) approach, which was modified from Malinowski's (1923) Phatic Communion original theory, was used to deductively analyse the data. The collected data in this study was qualitatively analysed using Atlas.ti software version 8. The Arabic drama yielded 91 small talk expressions and the Malay drama “Nur 2” yielded 100. The study’s findings show that there are similarities and differences in the use of small talk forms and functions between Arabs and Malays due to a variety of factors such as culture, gender, social status, context, and background of the conversation. Furthermore, the use of the forms and functions of small talk according to gender was found to be nearly identical with little variation. The findings of this study are expected to provide a clearer picture of the comparison of the use of small talk in two different cultures. It is also important to emphasise to the community the importance of cross-cultural communication, particularly in improving understanding of cultural differences and adapting to other cultures.